A library in CoCoA for implementing railway interlocking systems. - Hernando-Esteban, Antonio; Galán-García, José Luis; Padilla-Domínguez, Yolanda Carmen; Galán-García, María Ángeles (Elsevier, 2025)
In this paper, we propose a user-friendly library in CoCoA to address and completely resolve the challenges posed by the highly efficient and intriguing mathematical model introduced in Hernando et al., (2023) for implementing railway interlocking systems. Although the algebraic model (Hernando et al., 2023) allows for fast performance, it requires implementers and users to have a high level of mathematical knowledge, mastering concepts such as Gröbner bases, ideals, rings, and polynomials. This expertise is necessary to manually define ideals generated by numerous complex polynomials in multiple variables, which depend on the railway station’s topology, a process that can be both tedious and error-prone. To completely resolve these challenges, we have developed a CoCoA library that streamlines the implementation of interlocking systems using our mathematical framework, effectively eliminating manual errors. Consequently, thanks to the library we have developed and presented here, even users without mathematical knowledge can easily implement and manage a railway interlocking system.
https://openpolicyfinder.jisc.ac.uk/id/publication/11429
Keywords: Transporte ferroviario - Modelos matemáticos; Álgebra conmutativa; Railway interlocking system; Computer algebra; Decision making; Commutative algebra